Expression and co‐localization of RFRP‐3 and kisspeptin during breeding and non‐breeding season in the hypothalamus of male rhesus monkey (Macaca mulatta) - Safdar Khan; Bakhtwar Batool; Hira Zubair; Riffat Bano; Shakil Ahmad; Muhammad Shahab (Reproductive Medicine and Biology, 2022)
Abstract Propose The mechanism that underpins how RFRP‐3 and kisspeptin interacts are not fully understood in higher primates. This study therefore set out to assess RFRP‐3 and kisspeptin expression and their morphological interactions in the breeding, and in the non‐breeding period in monkey hypothalamus. Methods Eight mature male macaques (Macaca mulatta) in the breeding season (February; n = 4) and non‐breeding season (June; n = 4) were used. To reveal the expression and co‐localization of RFRP‐3 and kisspeptin, double‐labeled immunohistochemistry was performed. Testicular volume, sperm count, and plasma testosterone level were also measured to validate the breeding and non‐breeding paradigms. Results Testicular volume, plasma testosterone level, and sperm count showed a significant reduction during non‐breeding season. The number of kisspeptin‐positive cells was significantly increased during the breeding season (p < 0.05), whereas more RFRP‐3‐positive cell bodies were seen in the non‐breeding season (p < 0.01). Close contacts of RFRP‐3 fibers with kisspeptin cells showed no significant difference (p > 0.05) across seasons. However, co‐localization of RFRP‐3‐ir cell bodies onto kisspeptin IR cell bodies showed a statistical increase (p < 0.01) in non‐breeding season. Conclusion In higher primates, RFRP‐3 decreases kisspeptin drives from the same cells to GnRH neurons in an autocrine manner causing suppression of the reproductive axis during the non‐breeding period.